Carbohydrate supplementation and perceived exertion during prolonged running - Utter, A. C.; Kang, J.; Nieman, D. C.; Dumke, C. L.; McAnulty, S. R.; Vinci, D. M.; McAnulty, L. S. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of this study was to investigate the relationship between carbohydrate energy substrate and hormonal regulation on the perception of exertion during prolonged running. METHODS: Sixteen experienced marathoners ran on treadmills for 3 h at approximately 70% VO2max on two occasions while receiving 1 L x h carbohydrate (C) or placebo (P) beverages. Blood and vastus lateralis muscle biopsy samples were collected before and after exercise. RESULTS: The pattern of change in ratings of perceived exertion (RPE) over time was significantly different between C and P ingestion (P < 0.01) with attenuated RPE responses found in the latter part of the 3 h run. The pattern of change in the respiratory exchange ratio and carbohydrate oxidation rates were significantly greater (P < 0.01) in the C than P condition. Change in muscle glycogen content did not differ between C and P (P = 0.246). C relative to P ingestion was associated with higher plasma levels of glucose, insulin, and lactate and lower levels plasma cortisol. CONCLUSIONS: These data indicate that a lower RPE was associated with a higher carbohydrate oxidation, plasma glucose, and insulin levels, and lower plasma cortisol during prolonged running after C supplementation as compared with P feeding despite no differences in muscle glycogen content. These findings support a physiological link between RPE and carbohydrate substrate availability as well as selected hormonal regulation during prolonged running.